Effect of Growth Temperature and Mn Incorporation on GaN:Mn Thin Films Grown by Plasma-Assisted MOCVD - Budi Mulyanti; A. Subagio; F. S. Arsyad; P. Arifin; M. Barmawi; Irzaman Irzaman; Z. Jamal; U. Hashim (Institute for Research and Community Services (LPPM) ITB, 2008)
In this paper, the growth of GaN:Mn thin films by plasma-assisted metalorganic chemical vapor deposition (PAMOCVD) method is reported. The method used in this study, utilizes a microwave cavity as a cracking cell to produce nitrogen radicals, which in turn reduce the growth temperature. Trimethylgallium (TMGa), nitrogen (N2) and cyclopentadienyl manganese tricarbonyl (CpMnT) were used as a source of Ga, N and Mn, respectively, while hydrogen gas was used as a carrier gas for both TMGa and CpMnT. The effect of growth temperature and Mn incorporation on structural properties and surface morphology of GaN:Mn films are presented. The growth of GaN:Mn thin films were conducted at varied growth temperature in range of 625 oC to 700 oC and the Mn/Ga molar fraction in the range of 0.2 to 0.5. Energy dispersive of X-ray (EDX) and X-ray diffraction (XRD) methods were used to analyze atomic composition and crystal structure of the grown films, respectively. The surface morphology was then characterized using both atomic force microscopy (AFM) and scanning electron microscopy (SEM) images. A systematic XRD analysis reveal that maximum Mn incorporation that still produces single phase GaN:Mn (0002) is 6.4 % and 3.2 % for the film grown at 650 oC and 700 oC, respectively. The lattice constant and full width at half maximum (FWHM) of the single phase films depend on the Mn concentration. The decrease in lattice constant accompanied by the increase in FWHM is due to incorporation of substitutional Mn on the Ga sub-lattice. The maximum values of doped Mn atoms incorporated in the wurtzite structure of GaN:Mn as substitutional atoms on Ga sub-lattice are 2.0 % and 2.5 % at 650 oC and 700 oC, respectively. AFM and SEM images show that the film grown at lower growth temperature and Mn concentration has a better surface than that of film grown at higher growth temperature and Mn concentration.